Characteristics and treatment outcomes of tuberculosis patients who "transfer-in" to health facilities in Harare City, Zimbabwe: a descriptive cross-sectional study - Takarinda Kudakwashe C; Harries Anthony D; Mutasa-Apollo Tsitsi; Sandy Charles; Mugurungi Owen (BMC, 2012)
Abstract Background Zimbabwe is among the 22 Tuberculosis (TB) high burden countries worldwide and runs a well-established, standardized recording and reporting system on case finding and treatment outcomes. During TB treatment, patients transfer-out and transfer-in to different health facilities, but there are few data from any national TB programmes about whether this process happens and if so to what extent. The aim of this study therefore was to describe the characteristics and outcomes of TB patients that transferred into Harare City health department clinics under the national TB programme. Specific objectives were to determine i) the proportion of a cohort of TB patients registered as transfer-in, ii) the characteristics and treatment outcomes of these transfer-in patients and iii) whether their treatment outcomes had been communicated back to their respective referral districts after completion of TB treatment. Methods Data were abstracted from patient files and district TB registers for all transfer-in TB patients registered from January to December 2010 within Harare City. Descriptive statistics were calculated. Results Of the 7,742 registered TB patients in 2010, 263 (3.5%) had transferred-in: 148 (56%) were males and overall median age was 33 years (IQR, 26-40). Most transfer-in patients (74%) came during the intensive phase of TB treatment, and 58% were from rural health-facilities. Of 176 patients with complete data on the time period between transfer-in and transfer-out, only 85 (48%) arrived for registration in Harare from referral districts within 1 week of being transferred-out. Transfer-in patients had 69% treatment success, but in 21% treatment outcome status was not evaluated. Overall, 3/212 (1.4%) transfer-in TB patients had their TB treatment outcomes reported back to their referral districts. Conclusion There is need to devise better strategies of following up TB patients to their referral Directly Observed Treatment (DOT) centres from TB diagnosing centres to ensure that they arrive promptly and on time. Recording and reporting of information must improve and this can be done through training and supervision. Use of mobile phones and other technology to communicate TB treatment outcomes back to the referral districts would seem the obvious way to move forward on these issues.